RETRACTED: The Effect of Profitability and Firm Size on Firm Value with Capital Structure as an Intervening Variable in Lq 45 Companies on The Indonesia Stock Exchange For The Period 2014 – 2016 - Nurseha Nurseha; Elwisam Elwisam; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
The aim of the research was to find out the profitability and firm size on value firm with capital structure as intervening variable of LQ 45 firm in Indonesia Stock Exchange. The samples consist of 26 LQ 45 firm listed in Indonesia Stock Exchange during he period of 2014-2016, the research method use structural equation meodeling (SEM) with the help of software AMOS 21.0. The result of the research indicate that profitability, firm size and capital structure have a influence positive and significant on value firm. Profitability have a influence positive and not significant on capital structure and firm size have a influence positive and significant on capital structure. Futhermore, capital structure can function as intervening variable in the effect negative and significant of firm size but it does not effect of profitability in the effect positive and not significant.